Bilateral absence of the superior vena cava presenting with superior vena cava syndrome: A case report. Issue 8 (27th June 2019) - Zhang, Luni; Zhang, Li; Wang, Hui; Chen, Libo
Abstract: Bilateral absence of the superior vena cava (SVC) is a very rare congenital vascular anomaly that is mainly asymptomatic. In this report, we describe an adult male patient with bilateral absence of the SVC presenting with SVC syndrome. Blood from the upper body returned to the right atrium via the superficial thoracoepigastric veins, the great saphenous veins, the common femoral veins, and the inferior vena cava.